SarZ inhibits the hemolytic activity through regulation of phenol soluble modulins in Staphylococcus epidermidis - Chen, Xiao; Sun, Huiru; Wang, Wei; Wang, Han; Tan, Runan; Zhu, Tao (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundStaphylococcus epidermidis is an important conditionally pathogenic bacterium. SarZ, belonging to the SarA family protein, has been demonstrated in S. aureus to promote the expression of invasive virulence factors while inhibiting biofilm formation. However, the regulatory role of SarZ on S. epidermidis virulence is not completely understood.ResultsIn this study, we successfully deleted the sarZ gene by allelic replacement in S. epidermidis. The sarZ mutant strain exhibited remarkably increased hemolytic activity and drastically impaired biofilm formation, suggesting that SarZ is key regulator of virulence in S. epidermidis. Through butanol extraction of the spent medium and HPLC-MS/MS analysis, production of phenol soluble modulins (PSMs) possessing cytolytic effect was found to be elevated significantly in the mutant. Subsequent qRT-PCR experiments demonstrated that expression of the psm genes, especially the β-type, was upregulated dramatically in the mutant. Meanwhile, transcription of icaA gene responsible for biofilm formation was sharply diminished. The sarZ psmβ double mutant was further generated and displayed a significantly decreased hemolytic activity compared with the sarZ mutant. EMSA assays implied that recombinant SarZ protein can directly bind to the promoter regions of the psmβ and ica operon. DNase I footprinting assays further pinpointed two SarZ-binding sites on the psmβ operon promoter.ConclusionTaken together, the results confirmed that SarZ is a pivotal regulator of virulence in S. epidermidis and might respectively regulate the hemolytic activity and biofilm formation mainly by directly controlling the transcription of psm genes, particularly the β-type, and the ica operon.